To Be Or Knot To Be: A Rare Case Of Nasogastric Tube Knotting - Muzna Iftikhar, Muzna Iftikhar (Journal of Rawalpindi Medical College, 2020)
Nasogastric tube is a commonly used medium of enteral nutrition and gastric decompression in both medical and surgical patients. Nasogastric tube knotting is a rare complication with only a handful of cases found in literature. We report a case of a functional nasogastric tube that was discovered knotted upon removal and extracted safely under sedation.